Phase Behavior of Ascorbyl Palmitate Coagels Loaded with Oligonucleotides as a New Carrier for Vaccine Adjuvants - Ullio Gamboa, Gabriela Veronica (2016)
In this work, the phase behavior variations of an ascorbyl palmitate (Asc16) system in aqueous solution were analyzed when immunologically active hydrophilic compounds (CpG and OVA) were introduced. This study was carried out through optical polarizing microscopy (OPM) and differential scanning calorimetry (DSC) at different temperatures and over a broad range of concentrations. The combination of both techniques allowed the determination of a complete phase diagram which was compared with those built for Asc16-water system and it was demonstrated that fixed concentrations of hydrophilic compounds (300 and 24 µg/g for CpG-ODN and OVA respectively) generate two lamellar liquid crystals, a cubic liquid crystal phase, and also other aggregates. However, no changes were observed in the phase diagram in terms of formation of new mesophases. The aqueous phase behavior was also studied as a function of surfactant and temperature. DSC and Fourier transform infrared spectroscopy (FT-IR) measurements show differences in the free water and mainly in the secondary hydration layer, which confirm that the studied compounds are situated in the aqueous domain. The construction and analysis of Asc16 phase diagrams with a fixed concentration of CpG-ODN/OVA allows the comprehension of Asc16 phase behavior and could be easily adapted to other concentrations. Moreover, these findings could be extrapolated to other hydrophilic substances in aqueous solution introduced in liquid crystal phases since they follow a similar behavior as those reported in the literature.